e-WOM dan Strategi Promosi Pada Perilaku Impulsive Buying Konsumen Kuliner di Kota Solo Tahun 2021 Saat Pandemi Covid-19 - Lintang Pamugar Mukti Aji; Eka Dewi Sumarmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Covid-19 has caused the economy to decline, but people's consumption patterns have actually increased. During the PSBB (Large-Scale Social Restrictions) period, people are limited in their activities outside the home. However, many people still buy culinary products in a fairly high intensity, both online and offline. Culinary products are greatly affected by their existence due to Covid-19. Attractive marketing strategies such as promos and discounts are allegedly able to lure consumers to buy their products. In addition, a positive e-WOM can also make consumers interested in buying spontaneously. This study aims to determine the effect of e-WOM and culinary product marketing strategies on consumer impulsive buying behavior. Determination of the sample is done by purposive sampling technique. The sample used is 100 respondents. The test results show that promotional strategies and e-WOM have a positive and significant effect on consumers' impulsive buying behavior. The need for consumption is still high during this pandemic. Consumers still spend their money to consume culinary products such as snacks, bobba drinks, and other heavy meals online (online motorcycle taxis) or offline (eat in place/come in person).